Ebola virus surveillance in pigs presenting for slaughter in Uganda - Atherstone, Christine; Alonso, Silvia; Grace, Delia; Ward, M.; Dhand, Navneet; Mor, Siobhan M. (International Livestock Research Institute, 2016)
In 2008, Ebola Reston was discovered to infect pigs in the Philippines. Additionally, pigs have been experimentally infected with Ebola Zaire. Uganda has experienced five Ebola outbreaks with index cases unable to account for their source of infection. Over the past 30 years, the pig population in Uganda has increased by more than tenfold to meet growing consumer demand for pork. We are conducting research in regions of Uganda where pig keeping is an increasingly important livelihood strategy and where suitable ecological conditions exist for the emergence and persistence of pig-associated zoonotic diseases including Ebolavirus. Methods being used include repeated cross-sectional sampling of pigs presenting for slaughter during months when previous human Ebola outbreaks occurred in the country and when pig slaughter is known to increase. To determine effective locations for implementation of future surveillance and mitigation measures, pig trader network analysis to map pig trade volumes and routes is being done in conjunction with slaughterhouse surveillance. This is the first systematic, field-based study to determine if pigs are naturally infected with Ebolavirus in an area with previous outbreaks. Methods and findings to date will be shared.